The Rule of Sharia Financing Development to Improve One Pesantren One Product (OPOP) Program - Rofiqoh, Siti Nur Indah; Sulistyowati, Sulistyowati; Basya, Maziya Mazza; Alimin, Alimin; Ala’uddin, M. (International Conference on Islamic Studies, 2022)
This research aims to determine the development of sharia financing in upgrade OPOP program. This conceptual study used secondary data and descriptive analysis on sharia microfinance. It reviews 11 papers related to OPOP program in Google scholar, detected by Published or Perish (PoP) software. The exiting model shows that efficiency of sharia financing link OPOP program could be create pesantren empowerment, such as increase santri’s creativity, create product and open the labor market. The integration of sharia microfinance and pesantren will provide economic, social, and religion benefits. The several existing integrated model of sharia financing development to improve OPOP are cash waqf financing link OPOP, OVOP link OPOP, Sharia microfinance LKMS link OPOP and Islamic university link OPOP. The rule will provide economic, social, religion and ecological benefit, especially in reducing poverty. The recommendation encourages the other research to explore the role of sharia mudlorobah and ijaroh financing development exclude in upgrade OPOP Program.